Young people and everyday multiculturalism - Harris, Anita, 1968- (Critical youth studies ;, 2013)
"Unlike as with previous generations, diversity and multiculturalism are engrained in the lives of today's urban youth. Within their culturally diverse urban environments, young people from different backgrounds now routinely encounter one another in their everyday lives and negotiate and contest ways of living together and sharing civic space. What are their strategies for producing, disrupting and living well with difference, how do they create inclusive forms of belonging, and what are the conditions that militate against social cohesion amongst youth? This unique ethnography from education and cultural studies expert Anita Harris explores the ways young people manage conditions of cultural diversity in multicultural cities and suburbs, focusing particularly on how young people in the multicultural cities of Australia experience, define and produce mix, conflict, community and citizenship. This book illuminates rich, local approaches to living with difference from the perspective of a generation uniquely positioned to address this global challenge"--